Melatih Academic Hardiness Melalui Petualangan: Dampak Adventure Based Counseling pada Siswa - Setyowati, Aprilia; Partini, Siti; Wahyudi, Amien; Rahayu, Yuliyanti Indriani; Ardini, Fadhila Malasari; Widiatmoko, Mualwi (Universitas Mathla'ul Anwar Banten, 2024)
The learning problem of students who are active in various activities makes some students feel less responsive to facing new learning or activities to support the continuity of the learning process. The point that researchers see is the phenomenon of low academic hardiness in students. The aim of this research is to determine the impact of the Adventure Based Counseling (ABC) technical group counseling service to increase students' academic hardiness. The research method used was pre-experimental design with a one group pretest-posttest design model. The research subjects were 6 students using purposive sampling with existing criteria for subjects ranging from a low score of 28-56. This research uses the academic hardiness scale instrument. Data analysis used the Wilxocon test with a normality test and homogeneity test carried out first. Result of thi research is there is a difference in the pretest score and posttest score so it can be concluded that advnture based counseling technique group counseling services are effective in increasing students' academic hardiness